ISO 9001 aspects related to performance and their level of implementation - Jordi Castello Dalmau; Gerusa Gimenez; Rodolfo De Castro (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: In the last three decades, thousands of companies around the world have embraced the ISO 9001 standard in their quest to improve company performance and customer satisfaction. In recent literature, a number of authors have identified different "levels" of ISO 9001 implementation. This study aims to analyse these implementation levels in companies from the point of view of the customer, and provide guidelines for future improvement. Design/methodology/approach: Research was conducted based on the results of the second-party audits (SPAs) of 90 suppliers, (including component suppliers, assemblers, and wind farm operation and maintenance services), to one of the wind power industry's largest wind turbine manufacturers. The audits were carried out within the ISO 9001:2008 framework and conducted by one of this study's authors in his role as the wind turbine company's Director of Global Quality. Findings: Auditing suppliers plays a unique role in helping to isolate system weaknesses, identify opportunities and suggest areas for improvement. This study shows that, in terms of management commitment and culture and the good practices of an organization, ISO 9001 certified companies implement differing degrees of the standard. From the results of this research, a "road map" towards improvement can be established; one that allows companies in the sector to go beyond simply being accredited with the standard and instead to take advantage of ISO 9001 certification as a catalyst for change. Research limitations/implications: This article focuses only on the wind power sector, although its findings could be extrapolated to similar sectors of high technology and high levels of customization. Originality/value: While quality audits are a customary topic for academics and researchers, few contributions are related to SPAs and their impact on the quality control process of company suppliers. Primary data from the SPAs of suppliers (objective data collected by one of the paper's authors), was used here and is one of the most valuable aspects of this paper's contribution.
Keywords: 650; ISO 9001; supplier audit; second/third party audits; implementation level; factor analysis; wind power sector